Pengaruh Insentif terhadap Kepuasan Pekerja Perusahaan - Jerry Ong; Nathaniel; Aldo Marcolino; Jessalyn Tanubrata; Juliana Juliana (Kodepena Indonesia, 2020)
The study, entitled Worker Satisfication With Insentive did in PT Sewu Segar Primatama (Re.Juve). The aims is to determine the level of worker satisfication with incentive at the company. This research is theoretically expected to increase knowledge in the field of academic management in general. This research is a descriptive study with a quantitative approach. The sampling technique is done by simple random sampling. The sample size is 80 people. The results of this study states that incentives affect job satisfaction and it can be seen that the test show that there is an influence given with a regression model of 71.7% and the most influential indicator is a bonus if the work reaches the target. The results showed that the effect of incentives on workers is most sinifican. Suggestions for further research add other variables that affect worker satisfaction by combining the factors of other variables so that they can find out which variables are most influential on worker satisfaction.The result shows that it is true that incentive really affect worker’s satisfaction because the ability of incentive to explain satisfaction is 71,7% and the indicator that affect satisfaction the most is bonuses from company